Budget Buddy / Halimahton Borhan … [et al.] - Borhan, Halimahton; Irfan, Armin; Shauki, Roslizam; -, Muhammad Sharul; -, Najwa Adlina; -, Nurin Nazlah; -, Najwa Najiha (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
One of the life skills that every individual should possess in an unpredictable economic climate is the ability to manage their wealth wisely. Malaysians tend to struggle to achieve effective financial management of their wealth, which indirectly leads to various financial problems. Individuals feel like handling their funds is a misery which eventually makes them ignore the significance of achieving effective financial management. Aware of this situation in Malaysia, an idea was born to build a mobile application to help individuals manage their money effectively while enjoying the process. This application can assist users in tracking their monthly spending, assisting them in reaching their savings goals, offering investment guidance, and assisting them in making wise purchases. The most significant benefit this application offers to users is to make shopping sensible and wiser for them. The user can put this into practice by utilizing this software to conduct research before making a new purchase. These apps can assist users by providing a list of all the options open to them based on their constraints of financial condition and budget, using the personal financial background data that is available in the application. Furthermore, this app provides up-to-date information on markets that are appropriate for modest investments such as derivatives and equities. Finding all the information on one platform not only helps people make the best choice possible but also saves them time while conducting research. With all the features available, this idea could be a contender in the market. Not only is the interface user friendly, but also comes with all the resources needed to support users in managing their money. College students, employees, and small enterprises will have complete control over how they manage their wealth with Budget Buddy.